Clinical and microbiological profile of infections in patients undergoing general and orthopedic surgery at a teaching hospital in the Northeast (Research, Society and Development, 2024)
Objective: To evaluate the profile of patients affected by SSI in general and orthopedic surgery at a University Hospital in the Northeast. Methodology: This is a cross-sectional study, with a quantitative approach, carried out in the general medicine, orthopedics and traumatology sectors at a university hospital in northeastern Brazil, from January 2022 to July 2023. Results: Of 39 patients admitted to the surgical center 20 (51.28%) were male and 19 (48.71%) were female. The age group with the highest incidence of nosocomial infections associated with surgical site infections occurred in patients aged 60 years or less. Regarding topography, 22 (55%) of the patients had SSI - clear and 2 (5%) SSI - unclear. Regarding the sensitivity pattern, 3 (7.5%) pseudomonas aeruginosa sensitive to carbapenems, 2 (5%) Klebsiella pneumoniae sensitive to carbapenems and resistant to 3rd and/or 4th generation cephalosporins were identified. The microorganisms frequently found in the cultures were bacteria, represented by 3 (7.5%) cases of klebsiella pneumoniae, 1 (2.5%) aeromonas hydrophila. 22 (55%) patients were discharged, 5 (12.5%) were hospitalized and 1 (2.5%) died. Discussion: After analyzing the data covered in the study, the main causes that trigger SSI were highlighted, where they could be observed more frequently in the sectors monitored. Conclusion: The present study emphasizes the need for continuous updates for healthcare professionals regarding adequate patient care regarding the management and prevention of SSI.